SURGICAL TREATMENT TACTICS FOR OBSTRUCTION. - Kodirova Ziyodakhon Avazbek qizi; Akramova Nozima Akramovna (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Testicular torsion is an emergency condition that requires urgent diagnosis and surgical  intervention  to  prevent  ischemia  and  necrosis  of  the  organ.  The  paper systematizes modern data on surgical methods of treating this condition, analyzes their effectiveness  and  safety.  A  review  of  domestic  and  foreign  publications, including materials  from  the  scientific  databases  Google  Scholar,  Scopus  and  PubMed,  was carried out. Particular attention is paid to the factors affecting the prognosis, as well as methods of preventing relapses. It has been revealed that the key factor in successful treatment is timely surgical intervention performed within the first 6 hours from the onset of symptoms. The findings highlight the importance of educating healthcare staff and patients about the need to seek care early.